O desencontro entre o material didático e a diversidade cultural numa rede franciscana de ensino: um estudo de caso - Perillo, Paula Adriana (2009)
This paper develops a study about the didactic material elaborated by a private school system, based on the experience of one of its schools located in Pari, which is a neighborhood in the metropolitan region of São Paulo. For presenting uniqueness in its student body when compared with other schools, the research focuses initially on its local reality, analyzing the necessities and the existing practices when using this material in the classroom, with 5th to 7th grade students in Elementary School II. In the studied context there are two opposing forces: the curricular purpose of this teaching system presented in handouts configuring a standardization in the elaboration and proposition of the school curriculum, and a student body formed by foreign students, which presents a great ethnic cultural diversity, showing difficulties in expressing themselves in Portuguese as well as Brazilian students, who are the minority on this group. The argumentation of this study has been developed based on theorical support from authors as J. Gimeno Sacristán (1998, 1999, 2000, 2002, 2007), Paulo Freire (1981, 1982, 1996, 2000, 2001), Peter McLaren (1997, 2000), Michel Apple (2001, 2006), Antônio Flávio Moreira (1990, 2001, 2006), Tomaz Tadeu da Silva (2006, 2007). The study concludes there is a mismatch between the homogenizing didactic material and the cultural diversity found in the studied institution